Evolution of Care of Orbital Tumors with Radiation Therapy - Ioakeim-Ioannidou, Myrsini; MacDonald, Shannon M. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Orbital tumors are rare lesions comprising 0.1% of all tumors and less than 20% of all ocular diseases. These lesions in children and adults differ significantly in their incidence, tumor type, and treatment management. Although surgery and systemic therapies are commonly used in the management of these diseases, radiation therapy has become a widely used treatment for both benign and malignant tumors of the orbit. Radiotherapy is used as a definitive treatment to provide local control while avoiding morbidity associated with surgery for some tumors while it is used as an adjuvant treatment following surgical resection for others. For many tumors, radiation provides excellent tumor control with preservation of visual function. This article is dedicated for presenting the most common applications of orbital radiotherapy. A brief overview of the commonly available radiation therapy modalities is given. Dose constraint goals are reviewed and acute and long-term side effects are discussed. Orbital tumors covered in this article include optic glioma, ocular melanoma, retinoblastoma, orbital rhabdomyosarcoma, orbital lymphoma, and lacrimal gland tumors. Background information, indications for radiotherapy, and goals of treatment for each case example are described.
Keywords: radiation; proton therapy; IMRT; carbon-ion; melanoma; retinoblastoma; sarcoma; glioma; lymphoma; carcinoma